2012
DOI: 10.1021/ma3003856
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Isobutylene by AlCl3/Ether Complexes in Nonpolar Solvent

Abstract: The carbocationic polymerization of isobutylene (IB), co-initiated by AlCl3/ether complexes, has been reexamined and extended to different dialkyl ethers. In the absence of a proton trap, 2,6-di-tert-butylpyridine (DTBP), the polymerization of IB by the cumyl alcohol (CumOH)/AlCl3·nBu2O initiator/co-initiator system in dichloromethane/hexanes (80/20 v/v) at −40 °C gave high conversion to polyisobutylene (PIB) comprising exo-olefins with high selectivity, similar to that reported before by Vasilenko et al. , H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
124
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(133 citation statements)
references
References 14 publications
4
124
1
4
Order By: Relevance
“…The advantages of CumOH/AlCl 3 OBu 2 initiating system is the high reaction rate and the possibility to synthesize well‐defined PIBs with a cumyl group at the α‐end of polymer chain ( F n (Cum) = 75–90%) and an exo ‐olefin group at the ω‐end 23, 29. This approach opens an access to difunctional exo ‐olefin terminated PIB 30.…”
Section: Room Temperature Polymerization Of Ibmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of CumOH/AlCl 3 OBu 2 initiating system is the high reaction rate and the possibility to synthesize well‐defined PIBs with a cumyl group at the α‐end of polymer chain ( F n (Cum) = 75–90%) and an exo ‐olefin group at the ω‐end 23, 29. This approach opens an access to difunctional exo ‐olefin terminated PIB 30.…”
Section: Room Temperature Polymerization Of Ibmentioning
confidence: 99%
“…One significant drawback of the aforementioned initiating systems is the conducting of the polymerization in toxic chlorinated solvent. To replace CH 2 Cl 2 , the polymerization of IB with H 2 O/AlCl 3 OBu 2 initiating system was studied in different solvents (toluene, α,α,α‐trifluorotoluene, and n ‐hexane) 29, 31, 33. In toluene, the H 2 O/AlCl 3 OBu 2 initiating system afforded low‐molecular‐weight HR PIB ( M n = 1000−2100 g mol −1 ) with relatively narrow MWD ( M w / M n = 1.4−2.6) in a good yield (70−90% in 10 min) and even with a better functionality (90−94% of exo ‐olefin end groups) compared to CH 2 Cl 2 at T > 0 °C (Table 1).…”
Section: Room Temperature Polymerization Of Ibmentioning
confidence: 99%
“…12 Our recent reexamination of the polymerization of IB with the CumOH/AlCl 3 ·Bu 2 O initiator/co-initiator system in DCM/hexanes (80/20 v/v) at −40°C, previously reported by Kostjuk and co-workers, 9 revealed that CumOH is not an initiator in conjunction with AlCl 3 ·Bu 2 O and that the true initiator is adventitious water. 1 Similarly, in 100% hexanes at 0°C…”
Section: ■ Introductionmentioning
confidence: 99%
“…This was confirmed by the results of polymerization with water as the initiator in the presence or absence of impurities (Supporting Information Table S33–S36). In these experiments, water with EADC · CEE yields H + EADCOH − , which initiates the polymerization. By increasing the concentration of acetone, the polymerization rate decreases, and at [acetone] = [H 2 O] polymerization was absent.…”
Section: Resultsmentioning
confidence: 99%
“…The exo‐olefin terminated PIB is also referred to as “highly reactive” PIB (HR PIB), since it readily reacts with maleic anhydride in a thermal “ene” reaction to produce PIB succinic anhydride that can be converted to polyisobutenylsuccinimide, used as ashless dispersants. In the recent years, several research groups have reported on new catalyst systems for the synthesis of HR PIB . Some major drawbacks for the new HR PIB process systems include low process temperatures and/or use of polar chlorinated solvents that present serious limitations for industrial application .…”
Section: Introductionmentioning
confidence: 99%